Economic Impacts of the University of Florida and Affiliated Organizations in 2005-06 - Alan W. Hodges; W. David Mulkey; Thomas J. Stevens (EDIS)
FE699, a 21-page illustrated report by Alan W. Hodges, W. David Mulkey, and Thomas J. Stevens, evaluates the economic impacts of the University of Florida (UF) and its affiliated organizations on the state’s economy for the fiscal year 2005-06 using financial data together with regional economic models. Includes references. Published by the UF Department of Food and Resource Economics, October 2007.